Critical path analysis scheduling project with critical path method (CPM) using application microsoft project on type 78 house construction project - Suramli, Suramli; Rachman, Karenina Aulia; Dewi, Nanda Fitria; Novianda, Dea Salsa; Surahman, Surahman (Institute of Computer Science (IOCS), 2025)
This study presented the scheduling of a Type 78 house construction project using the Critical Path Method implemented in Microsoft Project. The research defined and sequenced all construction activities, estimated their durations based on field data, and modeled the schedule within the software. The CPM analysis revealed a total project duration of 120 days, with site preparation, structural framing, and roofing installation identified as the critical path activities. Non-critical tasks were found to have total floats of up to 15 days, indicating opportunities for resource reallocation and schedule compression. By simulating task overlaps and adjusting resource assignments, the study demonstrated a potential reduction in overall completion time by approximately 10%. The results confirmed that applying the Critical Path Method in Microsoft Project enhanced schedule visibility, facilitated proactive delay management, and provided practical guidance for optimizing residential construction timelines.